Modelling the Universiti Malaysia Pahang examination timetabling problem - Ling, Shing Chang; M. N. M., Kahar (Penerbit UMP, 2018)
This paper presents a study of the Universiti Malaysia Pahang (UMP) examination timetabling problem and its constraints. UMP currently situated in two campuses (Gambang and Pekan) which presents many challenges in producing examination timetable. The UMP examination timetabling problem consists of new constraints that have not been investigated before in the literature, that include scheduled exams into the appropriate campus. The additional constraints increase the level of difficulty in producing a high quality examination timetable. Additionally, having no formal mathematical model leads to difficulty in determining the quality of the produced examination timetable. This paper investigates the UMP examination timetabling constraints and develop the formal mathematical model to determine the quality of the generated examination timetable. The developed formal model able to evaluated the UMP examination timetable quality (produced by UMP’s proprietary system). The result reveals a high penalty value (bad quality) and unsatisfaction of the hard constraints.